2022
DOI: 10.1097/qai.0000000000002883
|View full text |Cite
|
Sign up to set email alerts
|

Neopterin Relates to Lifetime Depression in Older Adults With HIV on Suppressive Antiretroviral Therapy

Abstract: Background: Chronic inflammation contributes to the pathogenesis of depression in persons with HIV (PWH). Neopterin, a biomarker of HIV-related immune activation that partially normalizes with antiretroviral therapy (ART), correlates with major depressive disorder (MDD) and subclinical depressive symptoms in persons without HIV and acutely infected, young PWH. The sensitivity of neopterin, however, to both lifetime and current depression is poorly understood in older PWH on suppressive ART. Methods: Participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 65 publications
0
0
0
Order By: Relevance
“…Warriner et al reported that neopterin plasma levels might act as systemic immune markers useful in identifying treatment-resistant HIV-positive patients at greater risk of developing chronic depression [52] (Table 1). On the other hand, Saloner et al highlighted that plasma levels of neopterin were associated with lifetime MDD but not with ongoing depressive symptoms in such patients [71]. The authors concluded that the association might be related to the amino acid metabolism and neurotransmitter synthesis disruptions occurring in the inflammatory process.…”
Section: Studies Investigating Chronic Inflammatory Mechanismsmentioning
confidence: 99%
“…Warriner et al reported that neopterin plasma levels might act as systemic immune markers useful in identifying treatment-resistant HIV-positive patients at greater risk of developing chronic depression [52] (Table 1). On the other hand, Saloner et al highlighted that plasma levels of neopterin were associated with lifetime MDD but not with ongoing depressive symptoms in such patients [71]. The authors concluded that the association might be related to the amino acid metabolism and neurotransmitter synthesis disruptions occurring in the inflammatory process.…”
Section: Studies Investigating Chronic Inflammatory Mechanismsmentioning
confidence: 99%